2001
DOI: 10.1007/bf03026951
|View full text |Cite
|
Sign up to set email alerts
|

Development of an automated process sequence design system for multistage elliptical-Shaped deep drawing products

Abstract: This study defined the cross-section consisting of a round in the major axis and a straight line in the minor axis for deep drawing product as elliptical. A process sequence design for elliptical-shaped deep drawing products was diversely proposed according to shape, dimension, and specification of products. This study presents two approaches to the design of a preform, a key process for elliptical-shaped products: using a punch with a circular cross-section, and for geometrical similarity of the intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…He mentioned that elliptic cup with LDR of 2.05 was successfully produced. Many researchers conducted the deep drawing of elliptical cups either in multi-stages [16,18,20,21]or using hydroforming deep drawing process [8,12,22].…”
Section: Introductionmentioning
confidence: 99%
“…He mentioned that elliptic cup with LDR of 2.05 was successfully produced. Many researchers conducted the deep drawing of elliptical cups either in multi-stages [16,18,20,21]or using hydroforming deep drawing process [8,12,22].…”
Section: Introductionmentioning
confidence: 99%
“…A study was made on plasticity matrices with elastoplasts model for analyzing cup drawing and it was shown that if the reduction is too large, the tensile stresses in the drawn section will exceed the tensile strength and cause failure [1].Some investigators have studied the effect of process parameters on the residual stresses. They investigated the effect of the die edge radius and the punch diameter on the axial residual stresses in deep-drawn brass cup and observed that reduction the tool clearance, so that ironing occurs simultaneously with deep-drawing, cause a great reduction in the residual stresses [2,3,4].Sheet forming has many virtues that meet current needs very well, such as important of sheet formability, good surface quality, higher dimensional accuracy, reduction of the amount of spring-back compared to conventional sheet metal forming processes [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…angular deep-drawing die [2], it was shown that shape and dimension of parts is not enough accurate . Some investigator has studied effect of variable BHF on deep-drawing circular cup or rectangular box [3][4][5][6]. The hydro-mechanical deep drawing process has many remarkable advantages over conventional deep-drawing including the capability of forming more complicated products ,improving dimensional accuracy and surface quality [7], But ,this process is relatively slow.…”
Section: Introductionmentioning
confidence: 99%